2018
DOI: 10.1049/bsbt.2018.0001
|View full text |Cite
|
Sign up to set email alerts
|

Transitional behaviour between biphasic lubrication and soft elastohydrodynamic lubrication of poly(vinyl alcohol) hydrogel using microelectromechanical system pressure sensor

Abstract: The soft hydrogel material is expected for a candidate material as biomimetic artificial cartilage with synergistic functionalities of adaptive multimode lubrication. In boundary lubrication mode of hydrogel material, the biphasic lubrication mechanism cooperatively exerts its functionality. In hydrodynamic lubrication mode, it is preferable that the lubricating surfaces be impermeable to trap the fluid pressure in contact surfaces, whereas the actual biphasic material like a hydrogel is a permeable material w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…This occurs around the border between boundary and mixed lubrication. This onset condition designates the type of cartilage loading and the resulting magnitude of compressive/shear stresses are important to joint health [37], and have frictional importance to mechanical systems where minimal friction is desirable [38].…”
Section: Discussionmentioning
confidence: 99%
“…This occurs around the border between boundary and mixed lubrication. This onset condition designates the type of cartilage loading and the resulting magnitude of compressive/shear stresses are important to joint health [37], and have frictional importance to mechanical systems where minimal friction is desirable [38].…”
Section: Discussionmentioning
confidence: 99%
“…The figure also illustrates how the COF behavior alters with a change in polymer concentration (Fig 2a), polymer network (Fig 2b) and applied load (Fig 3c).The 30%-DN hydrogel that was worn at an applied load of 5N exhibited a low and stable COF behavior throughout the test. This behavior can be explained by the formation of biphasic lubrication(Sakai et al 2018). In all the other experiments, which involved either at a lower polymer concentration (15 wt%), a higher applied load (10 N) or a different polymer chain structure (SN), the COF was observed to increase for the first 10 min and then settle to a steady-state condition.…”
mentioning
confidence: 87%
“…In addition, the cross-linking of PVA can be achieved either by chemical or physical cross-linking. Because of excellent solubility and ultrahigh absorbance, PVA has been used as a humidity sensor. In addition to humidity, PVA-based hydrogels have been reported in pH and metal cation sensing. Among metal cation sensors, photonic crystal sensors composed of PVA-based hydrogel have been used for the detection of heavy metals. It has been reported that PVA hydrogel can be used as a glucose sensor. , The mechanical strength and flexibility of PVA hydrogel were improved for synthesizing pressure and strain sensors for motion detection. ,, …”
Section: Common Polymers For Hydrogel Sensor Applicationsmentioning
confidence: 99%
“…146,147 The mechanical strength and flexibility of PVA hydrogel were improved for synthesizing pressure and strain sensors for motion detection. 83,91,148 PEG is another synthetic polymer widely used for biomedical applications. The potential for applying PEG as a hydrogel has been studied for decades.…”
Section: Common Polymers For Hydrogel Sensor Applicationsmentioning
confidence: 99%